Oksidasi lipoprotein densitas rendah dan aterosklerosis - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
Abstract One of the earliest lesion of atherosclerosis is indicated by fatty streaks appearance. The fatty streak contains foam cell which are mostly derived from monocytes. The uptake of oxidatively modified low density lipoprotein (LDL) is not down regulated by the native LDL receptors. Oxidized LDL exhibits a chemotactic activity and a cytotoxicity. With the discovery the cells of the vascular system can induce lipid peroxidation in the LDL particle, it appears now more reasonable that reactive aldehydes including malonaldehyde are generated within the LDL particle itself. Subsequently it interact at or near the site of their origin with neighboring free amino groups and other functional groups of the apo-B polypeptide chain. Vitamin E is a true antioxidant in the LDL and is most likely located in the outer phospholipid layer with the chromanol ring facing the aqueous phase.